Visual Audio Communication Design on The Role of Information Technology on Student Life Style of Universitas Raharja - Andriyan, Wendy (ADI Journal on Recent Innovation, 2020)
Abstract The development of information technology is increasingly rapidly from past to now create a condition in which people want to get at the information source needs want to easily, quickly and accurately. In college, technology is indispensable to meet the needs of students in the learning process and look for the information needed to meet the needs of learning. The utilization of current technology can create a good condition and also not good that can affect one's personality. The utilization of current technology can create a good condition and also not good that can affect one's personality. The design of audio visual communication leads to the college environment as a media monitoring technology role that students use to create a good lifestyle in the college environment in the learning process. The design of audio visual communication leads to a college environment as a media monitoring technology role that students use to create a good lifestyle in a college environment in the learning process, So that it can create a high-quality and interactive community college in the use of technology as a learning medium. The purpose of this research is as a form of understanding the role of technology as a medium that helps the learning process in college students, whether the technology that has been used so far is enough to help students in learning and Whether it is well directed or not by the presence of a system of learning that uses technology in higher education. Keyword: Media, Video information, Visual Information